Neuerwerbungen 1980/81. (Köln : Museum Ludwig, 1981)
Aycock, Alice ; Baukhage, Gerd ; Carrà, Carlo ; Christo ; Exter, Alexandra Alexandrowna ; Freundlich, Otto ; Gontscharowa, Natalia ; Herkenrath, Peter ; Hockney, David ; Hofmann, Hans ; Jorn, Asger ; Kirili, Alain ; Kluzis, Gustav ; Ossipowna Kogan, Nina ; Krasner, Lee ; Krull, Germaine ; Lichtenstein, Roy ; Morandi, Giorgio ; Man Ray ; Rozanowa, Olga Waldimirowa ; Segal, Arthur ; Seidenstücker, Friedrich ; Sironi, Mario ; Smith, David ; Litterick Swan, Douglas ; Trier, Hann ; Tschaschnik, Ilja Grigorjewitsch
Neuerwerbungen 1980/81, Museum Ludwig, Köln, Austellung vom 12. Mai bis 28. Juni 1981
boek